Effects of danshensu on platelet aggregation and thrombosis: in vivo arteriovenous shunt and venous thrombosis models in rats. - Chen Yu (Public Library of Science (PLoS), 2014)
Danshensu, a type of dihydroxyphenyl lactic acid, is one of the most abundant active phenolic acids in the dried root of Salvia miltiorrhizae (Lamiaceae)--widely used traditional Chinese medicine. The effects of danshensu on platelet aggregation and thrombus formation in rats were examined using various methods. It was found that danshensu significantly reduced thrombus weight in 2 experimental thrombosis models; dose-dependent inhibition of adenosine diphosphate (ADP) and arachidonic acid (AA)-induced platelet aggregation occurred in normal and blood stasis-induced rats; Danshensu also significantly mitigated blood viscosity, plasma viscosity and hematocrit levels. Moreover, danshensu significantly inhibited venous thrombosis-induced expression of cyclooxygenases-2 (COX-2) rather than cyclooxygenases-1(COX-1) in the venous walls, down regulated thromboxane B2 (TXB2) and up regulated 6-keto prostaglandin F1α (6-keto-PGF1α), normalizing the TXB2/6-keto-PGF1α ratio. In addition, danshensu did not induce gastric lesions and even had protective effects on aspirin-induced ulcer formation at doses as high as 60 mg/kg. These findings suggest that the antithrombotic and antiplatelet aggregation effects of danshensu are attributed to its highly selective inhibition of COX-2 and ability to normalize the thromboxane A2(TXA2)/prostacyclin(PGI2) balance. These findings suggest that danshensu have great prospects in antithrombotic and antiplatelet therapy.